The Cambridge guide to mixed methods research for theatre and performance studies - Rae, Paul; Davis, Tracy C. 1960- (Cambridge University Press, 2024)
"We often know performance when we see it – but how should we investigate it? And how should we interpret what we find out? This book demonstrates why and how mixed methods research is necessary for investigating and explaining performance and advancing new critical agendas in cultural study. The wide range of aesthetic forms, cultural meanings, and social functions found in theatre and performance globally invites a corresponding variety of research approaches. The essays in this volume model reflective consideration of the means, processes, and choices for conducting performance research that is historical, ethnographic, aesthetic, or computational. An international set of contributors address what is meant by planning or designing a research project, doing research (locating and collecting primary sources or resources), and the ensuing work of interpreting and communicating insights. Providing illuminating and necessary guidance, this volume is an essential resource for scholars and students of theatre, performance, and dance."--Provided by publisher.